1985
DOI: 10.3382/ps.0640995
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Light Duration on Turkey Poult Performance and Adrenal Function

Abstract: Day-old tom poults were exposed to one of the following light treatments: 1) continuous incandescent light (24LL), 2) 23L:1D incandescent light, 3) 12L:12D incandescent light, or 4) natural day lengths only. Mortality was recorded daily. At Weeks 1, 2, 4, 6, and 8, after poult placement, body weights and feed consumption were measured. At each of these times, 10 poults were sacrificed from each treatment group for evaluation of plasma corticosterone. Day lengths utilized in this study had no consistent effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Adrenal glands have not been considered in any of the currently available PBPK models for chickens. In turkeys, adrenal glands constitute 0.019% of body weight based on two studies (Davis & Siopes, 1985 ; Hobbs & Moreng, 1976 ) as shown in Table 4 . Davis and Siopes ( 1985 ) conducted a study to determine the effect of light duration on turkey poult performance and adrenal function, in which the adrenal weight values were measured in 97 turkeys.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adrenal glands have not been considered in any of the currently available PBPK models for chickens. In turkeys, adrenal glands constitute 0.019% of body weight based on two studies (Davis & Siopes, 1985 ; Hobbs & Moreng, 1976 ) as shown in Table 4 . Davis and Siopes ( 1985 ) conducted a study to determine the effect of light duration on turkey poult performance and adrenal function, in which the adrenal weight values were measured in 97 turkeys.…”
Section: Resultsmentioning
confidence: 99%
“…In turkeys, adrenal glands constitute 0.019% of body weight based on two studies (Davis & Siopes, 1985 ; Hobbs & Moreng, 1976 ) as shown in Table 4 . Davis and Siopes ( 1985 ) conducted a study to determine the effect of light duration on turkey poult performance and adrenal function, in which the adrenal weight values were measured in 97 turkeys. The reported values ranged from 6.7 to 16.8 mg/100 g body weight for turkeys from one to eight weeks old under naturally occurring light duration.…”
Section: Resultsmentioning
confidence: 99%
“…Plasma samples were stored at -20 C and later assayed for CS by radioimmunoassay according to the methods of Satterlee et al (1980) and validated for turkey plasma (Davis and Siopes, 1985a). The intraassay coefficient of variation was 5.5%.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to hatching, CS levels increased in turkey embryos but declined through 6 h posthatching and remained low to 15 days of age (Wentworth and Hussein, 1985). Davis and Siopes (1985a) have shown that CS levels in torn poults remained low from hatch to 2 wk of age, but a 3 to 6-fold increase in circulating CS occurred between 4 and 8 wk of age. Davis and Siopes (1985b) examined the CS response of torn poults, from hatch to 21 days of age, after treatment with 10 IU/kg adrenocorticotrophic hormone (ACTH) or cold water immersion.…”
Section: Introductionmentioning
confidence: 96%
“…However, poultry in modern commercial facilities are reared in dim lighting of less than 5 lx to inhibit the activities of the birds and increase feed efficiency (Prescott et al, 2003) despite the U.K. Farm Animal Welfare Council (FAWC, 1992) recommendations of at least 20 lx. Under lighting of low intensity, numerous adverse effects may occur, e.g., increased adrenal weight, increased visual and leg problems, and decreased activity and livability (Siopes et al, 1984, Davis andSiopes, 1985). Thus, the light intensity distribution in broiler production facilities must be carefully managed with consideration of the preferences of broilers.…”
mentioning
confidence: 99%